Enhanced dielectric and ferroelectric properties in lead magnesium niobate-lead titanate ferroelectrics solid solutions by controlling the sintering protocols. Issue 16 (November 2020) - Jin, Li; Huang, Yunyao; Zhang, Leiyang; Jing, Ruiyi; Huang, Lida; Hu, Qingyuan; Guo, Dong; Wang, Guan; Wei, Xiaoyong; Lu, Xu; Wei, Fangbin; Liu, Gang
Abstract: Due to requirements for miniaturization and integration of electronic devices, ferroelectric materials with high dielectric permittivity would have potential applications in dielectric capacitors. In this work, (1− x )Pb(Mg1/3 Nb2/3 )O3 - x PbTiO3 (PMN- x PT) powders with x from 0.10 to 0.30 were obtained on the basis of a transitional columbite precursor method, while sintering processes were carried out under three protocols, i.e., (I) 1230 °C for 2 h, (II) 1230 °C for 16 h and (III) 1250 °C for 2 h. The temperature-dependent dielectric properties measured from 25 °C to 225 °C show that, under protocols II and III, the maximum permittivity ( ε m ) is significantly improved compared to those obtained via protocol I. A maximum ε m of 47036 is obtained in x  = 0.25 composition under protocol II, and the ε m is increased by more than 90% at the same composition. In the ceramics sintered through protocols II and III, the characteristics of both dielectric relaxations and dielectric dispersions are also enhanced. In addition, the ferroelectric and piezoelectric properties also show a marked increase in the composition of x  = 0.3. Our results suggest that the dielectric and ferroelectric properties of PMN- x PT solid solutions could be effectively enhanced by controlling the sintering protocols.